История политических и правовых учений: учебник для вузов / В. Г. Графский - Графский Владимир Георгиевич (Проспект, 2007)
Экземпляры: аб. (2008) / Инвентарный номер: 51829 / Цена: / Сис.шифр: 67 / Авт.знак: Г 78 / ГРНТИ: 10.11.91 / ББК: 67.1 я73